SOCIAL AND LABOR CONFLICT MANAGEMENT: UKRAINIAN AND FOREIGN EXPERIENCE - Nikita Nazarov (Сучасний стан наукових досліджень та технологій в промисловості, 2021)
The subject of study in the article is the process of socio-economic conflict management. The purpose of the work is to substantiate the theoretical provisions and methodological approaches in the management of labor conflicts as a form of social and labor relations based on Ukrainian and foreign experience. The following tasks are solved in the article: to investigate the essence and place of social and labor conflict in the system of social contradictions; provide a classification of conflicts in the social and labor sphere; to study the forms and methods of resolving social and labor conflicts: to analyze the success of conflict prevention in Ukrainian and foreign practice. The following methods are used: method of analysis and synthesis, classification-analytical method, abstract-logical method, historical-retrospective analysis and generalization. The following results were obtained: the concept of socio-economic conflict is clarified. The classification of conflicts is carried out, which gives an understanding of the nature and essence of conflict relations on the following grounds: the method of conflict resolution (antagonistic and compromise conflicts); spheres of conflict (political, social, economic, organizational conflicts); direction of impact (vertical and horizontal conflicts); degree of conflict confrontation (hidden and open conflicts); the number of participants in conflict interaction (intrapersonal, interpersonal, intergroup); needs (cognitive and interest conflicts). Structural and interpersonal methods for resolving conflict situations are defined. An analysis of the current state of resolution and prevention of labor conflicts in 2020 was conducted according to the National Service for Mediation and Reconciliation. Foreign experience in resolving labor disputes has proved the feasibility of developing the following ways to resolve labor disputes in Ukraine: with the help of special courts on labor and social security (sectoral justice); through civil proceedings in general courts; through conciliation and arbitration procedures. Conclusions: The analysis allowed to determine the essence of social and labor conflict as a form of social and labor relations at the micro, meso, and macro levels, which is manifested in the opposition of the subjects of the socio-economic sphere. Applying the gained world experience it is possible to reduce social tensions and to strengthen social and economic safety of the state.